Determination of the total and extractable fraction of Ni in lake sediments and natural waters of San Luis (Argentina) by FAAS using a simple solid phase extraction system - Escudero, Luis Ariel (2014)
An on-line nickel preconcentration and determination system implemented with flame atomic absorption spectrometry (FAAS) was developed. The nickel was retained on the inner walls of a column filled with ethyl vinyl acetate (EVA). The EVA was used as sorbent material for on-line solid-phase extraction (SPE) in the absence of complexing agent. The effects of sampling volume, elution conditions, sample pH and flow rate on the Ni extraction were studied. The analytical efficiency parameters obtained with this methodology were: enrichment factor (EF) of 46 times for a preconcentration time of 120 s, the limit of detection (LOD) was 3.78 μg L− 1, and the precision for six replicate determinations (repeatability conditions) at 20 μg L− 1 Ni concentration was 4.38% relative standard deviation. The sampling frequency for the proposed system was about 20 samples/h. The optimized procedure was applied to the determination of Ni in natural water and lake sediment samples.